2013
DOI: 10.1038/ncomms2961
|View full text |Cite
|
Sign up to set email alerts
|

Urban characteristics attributable to density-driven tie formation

Abstract: Motivated by empirical evidence on the interplay between geography, population density and societal interaction, we propose a generative process for the evolution of social structure in cities. Our analytical and simulation results predict both super-linear scaling of social-tie density and information contagion as a function of the population. Here we demonstrate that our model provides a robust and accurate fit for the dependency of city characteristics with city-size, ranging from individual-level dyadic in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
168
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(185 citation statements)
references
References 36 publications
16
168
1
Order By: Relevance
“…These include many creative productivities and infrastructure volumes [14][15][16][17] such as the gross domestic product (GDP), the number of patents, human online activities [18], prosocial behaviors [19], quantities related to highway systems [20], the number of crimes [21], the number of supply stations [22], and emissions of CO 2 [23] and NO 2 [24]. There exist several models explaining such allometric scaling behavior [25][26][27][28] and fluctuations around average power-law relations [29][30][31]. These findings allow us to write an urban indicator Y as a function of the population size N as…”
Section: Introductionmentioning
confidence: 99%
“…These include many creative productivities and infrastructure volumes [14][15][16][17] such as the gross domestic product (GDP), the number of patents, human online activities [18], prosocial behaviors [19], quantities related to highway systems [20], the number of crimes [21], the number of supply stations [22], and emissions of CO 2 [23] and NO 2 [24]. There exist several models explaining such allometric scaling behavior [25][26][27][28] and fluctuations around average power-law relations [29][30][31]. These findings allow us to write an urban indicator Y as a function of the population size N as…”
Section: Introductionmentioning
confidence: 99%
“…The aggregated networks each have a density of 1, that is, the networks are completely connected with every region having some level of communication with every other region. This high level of connectivity makes these kind of networks unlike the majority of networks studied in relation to information diffusion [8], [42], [49]- [52].…”
Section: Network Structurementioning
confidence: 99%
“…Relatedly, Pan et al [8] hypothesise that the superlinear scaling of urban characteristics such as wealth and rate of innovation with population size can be attributed to social tie density, which in turn enables increased flow of information through the population. To test this, they simulated information flow using the SI model in synthetic city-wide social networks and, in support of their hypothesis, found that diffusion rates also scale super-linearly with population size.…”
Section: B Information Diffusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pentland and a team of colleagues investigated this phenomenon with a computer model that simulated social ties in virtual cities of from 10 thousand to 10 million residents (6). They found that, as the population density grew, the number of interactions each individual could have increased by an exponential factor.…”
Section: Society In High Resolutionmentioning
confidence: 99%